Speech perception in patients submitted to cochlear reimplantation - Costa, Lucas Bevilacqua Alves da (2024)
Purpose: To analyze the performance of auditory speech perception (PF) after cochlear implant (CI) replacement surgery and associations with age, times of use of the first CI, deprivation, recovery and use of the second device. Methods: The retrospective study analyzed the medical records of 68 participants reimplanted from 1990 to 2016, and evaluated with PF performance tests, considering as a reference, the greater auditory capacity identified during the use of the first CI. Also analyzed were: Etiology of hearing loss; the reasons for the reimplantation; device brands; age range; sex; affected ear; age at first implant; time of use of the first CI, deprivation, recovery and use of the second device. The analyzes followed with the Chi-Square and Spearman, Mann-Whitney and Kruskal-Wallis tests (CI=95%; p <= 0.05; Software SPSS (R).v22). Results: Most were children with hearing loss due to idiopathic causes and meningitis. Abrupt stoppage of operation was the most common cause for device replacement. Most cases recovered and maintained or continued to progress in PF after reimplantation. Adults have the worst recovery capacity when compared to children and adolescents. The PF capacity showed a significant association (p <= 0.05) with: age at first implant; time of use of the first and second CI. Conclusion: Periodic programming and replacement of the device when indicated are fundamental for the maintenance of auditory functions. Being young and having longer use of implants represent advantages for the development of speech perception skills.